Study on the Cellulase-Immobilized Efficiency of Polyethylene-Glycol-Modified Chitosan as a Carrier - Nong, Xiang; Wu, Hong; Xie, Bin; Hao Xu, Cheng; Liang, Zi (Asian Journal of Chemistry, 2012)
To study the cellulase-immobilized efficiency of polyethylene glycol (PEG)-modified chitosan as a carrier, we evaluated the quantity, optimum temperature, optimum pH and Michaelis constant of immobilized enzymes that used such a carrier. The results showed that the immobilized enzymes which used the polyethylene glycol-modified chitosan as a carrier increased in quantity and showed improvements in optimum temperature from 5 to 10 ºC (P < 0.05) and optimum pH (P > 0.05). The Michaelis constants were 0.4693 g/L (KmM) and 0.4848 g/L (KmO), corresponding to y(M) = 1.0076x + 2.1472 and y(O) = 1.1086x + 2.287, respectively. Thus, utilizing polyethylene glycol-modified chitosan as a carrier can improve the efficiency of cellulase immobilization.